2011
DOI: 10.3762/bjnano.2.32
|View full text |Cite
|
Sign up to set email alerts
|

Determination of object position, vortex shedding frequency and flow velocity using artificial lateral line canals

Abstract: SummaryThe lateral line system of fish consists of superficial neuromasts, and neuromasts embedded in lateral line canals. Lateral line neuromasts allow fish to sense both minute water motions and pressure gradients, thereby enabling them to detect predators and prey or to recognize and discriminate stationary objects while passing them. With the aid of the lateral line, fish can also sense vortices caused by an upstream object or by undulatory swimming movements of fish. We show here that artificial lateral l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 30 publications
0
72
0
Order By: Relevance
“…The sensing of the turbulent wake behind a cylinder using a virtual sensor has been described previously by Akanyeti et al [10], and object identification using pressure sensors has been completed for static arrays [11][12][13]. Further wake navigation algorithms have been previously developed based on the predicted pressure signal [14].…”
Section: Introductionmentioning
confidence: 99%
“…The sensing of the turbulent wake behind a cylinder using a virtual sensor has been described previously by Akanyeti et al [10], and object identification using pressure sensors has been completed for static arrays [11][12][13]. Further wake navigation algorithms have been previously developed based on the predicted pressure signal [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigated this issue [51,82]. However, experiments were done mainly in open frame flow tanks.…”
Section: Cross-correlation Flow Metering: Estimated Bulk Flow Rates Fmentioning
confidence: 99%
“…Therefore, we used the fish lateral line canal system as a model for our bioinspired flow sensor. Previously, we developed artificial CNs made of polydimethylsiloxane (PDMS) and showed that artificial CNs can detect bulk fluid flow and the water motions caused by a vibrating sphere [51,[67][68][69]. With an array of eight artificial CNs, we determined the flow velocity from fluctuations superimposed on the bulk water flow [51].…”
Section: Biomimetic Flow Sensors: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations